COMPARISON BETWEEN MINI-BAL AND BAL RESULTS AMONG ICU PATIENTS WITH PREDOMINANT RIGHT LOWER LOBE PNEUMONIA - Ahmad, Anam; Ali Naqvi, Syed Mazhar; Nazir, Humaira; Sarwar, Noma; Aslam, Waqas; Tariq, Rabia (Infectious Diseases Journal of Pakistan, 2023)
Background: Bacterial pneumonia is one of the public health concerns with high ICU admissions, morbidity and mortality in individuals of all ages worldwide. The diagnosis in intensive care unit (ICU) settings poses challenges, primarily obtaining rapid and reliable microbiological confirmation. Objective of the present study is to compare the results of mini-BAL and BAL among ICU patients with predominant right lower lobe pneumonia. Material and Methods: This Prospective randomized comparative cross-sectional study as done Medical ICU, Services Hospital, Lahore – 1 year. The study was carried out after approval from the institute's ethics committee. Our study had 66 participants, 33 in each group. Each group of patients was assigned at random. The first group had the BAL procedure, whereas the second group received the mini-BAL procedure. Both groups' demographic, clinical, laboratory, bacteriological, and mycological data were obtained. SPSS version 23 was used to analyse the data collected. Mean, standard deviation, frequency, and percentages were utilised in descriptive statistics. The Chi square test was also used to compare groups. Cut off set to p<0.05. Results: The BAL technique isolated bacteriological pathogens in 13(39.4%) patients and mini-BAL technique isolated bacteriological pathogens in 15(45.5%) patients. The BAL technique isolated mycological pathogens in 12(36.4%) patients and mini-BAL technique isolated mycological pathogens in 14(42.4%) patients. There was no statistically significant difference among the two procedures. (p>0.05) Conclusion: In the mini-BAL group, the frequency of isolation of bacteria and mycological pathogens is slightly higher. Although there was no statistically significant difference, we propose that mini-BAL be used instead BAL because it is less invasive. Key Words: Comparison, Mini-BAL, BAL ICU patients, Right lower lobe, Pneumonia